Conflicting Selves: Family Owners' Multiple Goals and Self-Control Agency Problems in Private Firms. (May 2018) - De Massis, Alfredo; Kotlar, Josip; Mazzola, Pietro; Minola, Tommaso; Sciascia, Salvatore
This study examines the self–control agency problems associated with family ownership in private firms. Theorizing that family owners' inner conflicts between economic and non–economic goals lead to competing preferences in the allocation of financial resources, we predict that the relationship between financial slack and firm profitability is contingent on factors that increase the potential salience of either economic or noneconomic goals for family owners. Accordingly, our findings suggest that self–control is a separate source of agency costs in private firms and that family ownership is not as crucial as owners' goals in predicting the impact of financial slack on firm profitability.